Physical characterization of equal-mass binary near-Earth asteroid 2017 YE5: a possible dormant Jupiter-family comet. Issue 4 (24th August 2021) - Monteiro, F; Rondón, E; Lazzaro, D; Oey, J; Evangelista-Santana, M; Arcoverde, P; De Cicco, M; Silva-Cabrera, J S; Rodrigues, T; Santos, L B T
ABSTRACT: Photometric observations of the nearly equal-mass binary near-Earth asteroid 2017 YE5 were carried out at the Observatório Astronômico do Sertão de Itaparica (OASI, Brazil) and at the Blue Mountains Observatory (BMO, Australia) between 2018 July and August, shortly after it made a close approach to Earth in 2018 June. These observations allowed to determine an orbital period of the system in good agreement with the result of the radar observations. Our results also indicate that the 2017 YE5 system is not fully locked in a synchronous spin–orbit resonance, as there is a possible asynchronous component or tumbling rotator in the system. Additional data obtained at the Observatorio Astronómico Nacional de San Pedro Mártir (OAN-SPM, Mexico) in 2018 August allowed to derive the colour indices and the low-resolution spectrum, which indicate that the object has a very reddish surface similar to the outer Solar system objetcs. This is consistent with a dark albedo of about 3 per cent, derived from an effective diameter of the combined components and an absolute magnitude of 19.2. Infrared data obtained at the NASA's Infrared Telescope Facility exhibit a thermal emission in the 2.5 $μ$ m range for which a low albedo of 2–4 per cent was adjusted by applying a thermal model. Regarding to the taxonomic classification, we found that the 2017 YE5 is a D-type in the Bus-DeMeo taxonomy. Therefore, according to our results and considering that the 2017 YE5 system has a typical comet orbit ( T J = 2.87), we suggest that it is a dormant Jupiter-family binary comet.